2017
DOI: 10.1016/j.cpc.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Fuchsia : A tool for reducing differential equations for Feynman master integrals to epsilon form

Abstract: We present Fuchsia -an implementation of the Lee algorithm, which for a given system of ordinary differential equations with rational coefficients

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 27 publications
(37 reference statements)
0
124
0
Order By: Relevance
“…We made several attempts to produce such a basis using the publicly available programs Fuchsia [36] and CANONICA [37]. We were not able to obtain a canonical basis for our master integrals for all sectors.…”
Section: Jhep03(2018)048mentioning
confidence: 99%
“…We made several attempts to produce such a basis using the publicly available programs Fuchsia [36] and CANONICA [37]. We were not able to obtain a canonical basis for our master integrals for all sectors.…”
Section: Jhep03(2018)048mentioning
confidence: 99%
“…This corresponds to a change of basis in the fibre. Methods to find the right transformation have been discussed in [15][16][17][18][19][20][21][22][23][24].…”
Section: Review Of Differential Equations and Multiple Polylogarithmsmentioning
confidence: 99%
“…systems with an associated matrix where the dependence on the space-time dimensions is decoupled from the kinematics [8,9], has led to a substantial improvement of the system-solving strategy [10][11][12][13][14][15][16][17][18][19], and to the availability of many novel results. In the case of Feynman integrals that depend on several scales, we have shown that the Magnus exponential [11] is an efficient tool to derive MIs obeying canonical systems starting from a basis of MIs that obey systems of DEs whose matrix has a linear dependence on the space-time dimension [20][21][22].…”
Section: Jhep04(2017)008mentioning
confidence: 99%